Primeros ensayos vinculados a la vitrificación de residuos líquidos de alta actividad - Pahissa, Marta; Ramallo, T.; Ipohorski, Miguel; Palacios, Tulio Alfredo; Mari, E.; Hense, C. (Comisión Nacional de Energía Atómica; Argentina, 1987)
Fil: Pahissa, Marta Comisión Nacional de Energía Atómica; Argentina